A polymorphism upstream MIR1279 gene is associated with pericarditis development in Systemic Lupus Erythematosus and contributes to definition of a genetic risk profile for this complication. (July 2017) - Ciccacci, C; Perricone, C; Politi, C; Rufini, S; Ceccarelli, F; Cipriano, E; Alessandri, C; Latini, A; Valesini, G; Novelli, G; Conti, F; Borgiani, P
Recently, a study has shown that a polymorphism in the region of MIR1279 modulates the expression of the TRAF3IP2 gene. Since polymorphisms in the TRAF3IP2 gene have been described in association with systemic lupus erithematosus (SLE) susceptibility and with the development of pericarditis, our aim is to verify if the MIR1279 gene variability could also be involved. The rs1463335 SNP, located upstream MIR1279 gene, was analyzed by allelic discrimination assay in 315 Italian SLE patients and 201 healthy controls. Moreover, the MIR1279 gene was full sequenced in 50 patients. A case/control association study and a genotype/phenotype correlation analysis were performed. We also constructed a pericarditis genetic risk profile for patients with SLE. The full sequencing of the MIR1279 gene in patients with SLE did not reveal any novel or known variation. The variant allele of the rs1463335 SNP was significantly associated with susceptibility to pericarditis ( P = 0.017 and OR = 1.67). A risk profile model for pericarditis considering the risk alleles of MIR1279 and three other genes (STAT4, PTPN2 and TRAF3IP2) showed that patients with 4 or 5 risk alleles have a higher risk of developing pericarditis ( OR = 4.09 with P = 0.001 and OR = 6.04 with P = 0.04 respectively). In conclusion, we describe for the first time the contribution of a MIR1279 SNP in pericarditis development in patients with SLE and a genetic risk profile model that could be useful to identify patients more susceptible to developing pericarditis in SLE. This approach could help to improve the prediction and the management of this complication.